A REVIEW ON PRACTICAL ASPECTS OF PRINCIPLES OF ROGANUTPADNEEYAM - Choudhary Archana; Singh Rita (International Journal of Applied Ayurved Research, 2018)
Health is the supreme foundation for the achievement of happy life. The body constitutes the root cause of the well being of the individual and the very production of the body is dependent upon the individual self. Thus one should maintain the body leaving everything else for if there is no body, there is nothing that can be made available to the individual. To have a happy, long and disease free life has been an earnest desire of man, from the time immemorial. To achieve this first and foremost aim, Ayurveda has advocated principles of roganutpadneeyam i.e. certain rules pertaining to daily regimen, diet, ritucarya, sadvritta, adharniya vega etc. for the preservation of health. The idea of health put forth by Ayurveda is so perfect and comprehensive in itself that it not only proves the proverb ‘Health is wealth’ but also establishes an understanding of positive healthy life as a whole and its worldly achievements. “Swasthasya swasthya rakshanam” in Ayurveda propounds an unique objective to make human life better, longer, more capable and useful, happier. Its purpose is to make time in which we live, and the future, a better time for all.